On a feedback-feedforward identification control algorithm for feedback active controlled structures - Viet, La Duc; Anh, Nguyen Dong (Vietnam Journal of Mechanics, 2007)
Linear quadratic regulator (LQR) is an effective method of feedback active control theory. However, the LQR control is not truly optimal because it is only a feedback algorithm, i.e. the external excitation term is ignored in the optimal equation. In a previous paper [1], the identification algorithm is presented for feedback active controlled systems to identify the excitation from the structural response measured. The aim of this paper is to propose a feedback-feedforward control algorithm using the identified excitation to improve the classical LQR control. A numerical simulation is applied to an eight story building subjected to base acceleration and controlled by active mass damper system.